PENGARUH INTERNAL MARKETING TERHADAP JOB SATISFACTION DENGAN EMPLOYEE ENGAGEMENT SEBAGAI PEMEDIASI ( Survei Pada Karyawan PT. Bank Mandiri (Persero) Tbk Area Solo) - Marjono, Sri; Suddin, Alwi; Suprayitno, Suprayitno (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
The purpose of this study is to analyze the significance of the influence of internal marketing on job satisfaction, the significance of the influence of internal marketing on employee engagement, the significance of the effect of employee engagement on job satisfaction and the role of employee engagement in mediating the influence of internal marketing on job satisfaction on PT employees. Bank Mandiri (Persero) Tbk Solo Area. The population of this study is employees of the units of PT. Bank Mandiri (Persero) Tbk under the coordination of the Solo Area. Samples were taken as many as 97 respondents. Data obtained by distributing questionnaires to research samples. Analysis tool with research instrument test, classic assumption test and path analysis. While for the influence of mediation, testing uses Sobel test. The results of the study show that internal marketing has a significant effect on job satisfaction; internal marketing has a significant effect on employee engagement; employee engagement has a significant effect on job satisfaction and employee engagement does not mediate the influence of internal marketing on job satisfaction.